Racial and gender variations in adult hip morphology. - Lavy, C; Msamati, B; Igbigbi, P (2003)
Pelvic X-rays of 99 adult patients (198 hips) were analysed in 58 men and 41 women to determine the morphology of the adult hip in Malawians. For each hip the centre edge angle of Wiberg, the acetabular angle of Sharp and the acetabular head index were measured. For each parameter, women were more dysplastic than men, and for the acetabular angle of Sharp there was a significant gender difference ( p<0.05, t test). Our figures were compared to those of Fujii et al. who had measured the same parameters in Japanese and British hips. His results taken with ours showed that within a racial group, women were more dysplastic that men and that Japanese hips were more dysplastic than British hips, which were in turn more dysplastic than Malawian hips.